Velocity profiles in a free-surface flow system with a hydraulic rotational vortex - Arteaga Marín, Juan (2018)
Free-surface flow system are characterized by the exposure of an area to the atmosphere. The flow velocity in these systems is conditioned by factors such as the roughness of the materials which forms the section that produces friction forces opposed to the fluid movement. The purpose of this study is to provide an overview of the distribution of velocity lines in a free-surface flow (channel) which includes a hydraulic rotational vortex. Gauging and velocity were measured in nine sectors of the experimental flow system; seven were set in the section of the channel that feeds the prototype and two in the rotational vortex. Flow velocities were taken with the Pitot tube at various points along each sector. Velocity distributions were made with the aid of a computer application for data interpolation and were tested through a computational-fluid-dynamics (CFD) method. The results obtained allowed to visualize the flow’s maximum velocities location in the sections of the channel and the rotational vortex; and to check the flow’s velocity variation in accordance with the gradual changes of the dimensions and features in each driven section. In addition, a significant increase of fluid velocities when producing the rotational and vortex flow was observed.